PERBANDINGAN KEJADIAN PNEUMONIA NOSOKOMIAL PADA PASIEN STROKE YANG DIRAWAT DI STROKE CORNER DENGAN YANG DIRAWAT DI BANGSAL - Laura O. Siagian*, Aldy S. Rambe**, Hasan Sjahrir** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION PNEUMONIA IS A COMMON COMPLICATION AFTER STROKE THAT MAKE THE RECOVERY MORE DIFFICULT HIGH INCIDENCE OF NOSOCOMIAL INFECTION ARE THE MOST COMMON PROBLEM IN THE HOSPITAL